POTENTIAL OF PLANT-DERIVED ANTIMICROBIAL COMPOUND AGAINS MULTI-DRUG RESISTANT TUBERCULOSIS (MDR-TB): A LITERATUR REVIEW - Pauzi, Rizqi Yanuar; Ihtiaringtyas, Suci; Wahyudin, Wahyudin (Medical and Health Journal, 2024)
Antibiotic resistance is currently a global challenge, especially in the healthcare. Tuberculosis is a disease caused by Mycobacterium tuberculosis that has developed to resistant strains against antibiotic. Multi-drug resistant tuberculosis (MDR-TB) is a Mycobacterium strain that is resistant to first-line TB drugs such as isoniazid and rifampicin. More than 10 million people suffer from TB every year, while MDR-TB sufferers in 2022 about 410,000 people. Treatment for MDR-TB patients has side effects in the form of toxicity. Plant-derived antimicrobial compounds have the potential to inhibit the growth of MDR-TB so they can be used as alternative treatments. Recent studies discuss several potential plant compounds against MDR-TB in a country. This article presents several antimicrobial compounds from various plant species from various countries against MDR-TB. The results of the study showed that around 20 compounds from various plant species had the potential to inhibit MDR-TB. These compounds can be developed further, especially by examining their side effects on the body so that they can be used as an alternative treatment for MDR-TB.